A A Policy Evaluation of Permendikbudristek No. 12 of 2024: Scout Extracurricular Activities and Students’ Physical Condition: Evaluasi Kebijakan Permendikbudristek No. 12 Tahun 2024: Kegiatan Ekstrakurikuler Pramuka dan Kondisi Fisik Peserta Didik - Fais, Ahmad; Budi Purwoko; Mufarrihul Hazin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Extracurricular activities provide opportunities for outstanding students to explore and develop their talents and creativity in applying scouting values ​​to form eight dimensions of graduate profiles, especially the health dimension. Evaluation of the policy of Permendikbudristek Number 12 of 2024 Chapter 1 general provisions article 24 which contains student participation in extracurricular activities is voluntary. Evaluation of the implementation of this policy has an impact on the provisions for participation in scouting extracurricular activities. There are schools that still follow the old provisions, namely requiring students to take part in scouting extracurricular activities. The purpose of this study was to evaluate the scouting extracurricular policy on the formation of eight dimensions of graduate profiles, especially the health dimension of students at SDN Ngagel 1 Surabaya. Qualitative approach method, with descriptive research type. Data collection techniques were carried out through observation and interviews. The data obtained were analyzed by the process of data reduction, data visualization (data presentation) and data verification stages. The results of this study are that scouting extracurricular activities can apply scouting values ​​that have the same meaning as the eight dimensions of graduate profiles that can help students develop character so that they can be applied in real life.